Effects of Sodium Hydroxide, Sodium Hypochlorite, and Gaseous Hydrogen Peroxide on the Natural Properties of Cancellous Bone. Issue 7 (4th February 2013) - Bi, Long; Li, De‐Cheng; Huang, Zhao‐Song; Yuan, Zhi
Abstract Processed xenegeneic cancellous bone represents an alternative to bone autograft. In order to observe the effects of present prion inactivation treatments on the natural properties of xenogeneic cancellous bones, we treated bovine bone granules with sodium hydroxide (NaOH), sodium hypochlorite (NaOCl), and gaseous hydrogen peroxide (gH2O2) respectively in this study. The microstructure, composition, and mineral content of the granules were evaluated by scanning electron micrograph, energy dispersive X‐ray spectroscopy, ash analysis, and micro‐computed tomography. The biomechanical property was analyzed by a materials testing machine. The cytocompatibility was evaluated by using a mouse fibroblast cell line (3T3). The microstructure, organic content, and mechanical strength were dramatically altered at the surface of bone in both NaOH‐ and NaOCl‐treated groups, but not in the gH2O2‐treated group. Compared with the gH2O2‐treated group, attachment and proliferation of 3T3 were reduced in either NaOH‐ or NaOCl‐treated groups. As the consequence, gH2O2 treatment may be a useful approach of disinfection for the preparation of natural cancellous bone with well‐preserved structural, mechanical, and biological properties.